Peran Orangtua Dalam Melanjutkan Pendidikan Peserta Didik - Sabirin, Ayuni; Nurishlah, Laesti; Samadi, Mochammad Ramdan (Prodi PGMI STAI Sabili Bandung, 2024)
The role of parents in a child's education is pivotal and profoundly influential. Negative parental attitudes towards higher education can significantly impede the continuity of their child's academic pursuits. Research indicates that some parents perceive higher education as unimportant and a mere waste of time. They prioritize immediate employment over continued education, viewing it as more beneficial, especially given the high unemployment rate among college graduates. This mindset is often shaped by adverse economic conditions, low educational backgrounds of the parents, and the prohibitive costs associated with higher education. Parents struggling with economic hardship tend to prioritize immediate needs, such as securing employment, over the perceived long-term benefits of higher education. These obstacles render higher education seemingly irrelevant and less advantageous in the short term.